RELEVANSI PERDA NOMOR 3 TAHUN 1991 DALAM PEMBANGUNAN PARIW ISATA BUDAYA BALI - Teguh Hadi Sukarno (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2007)
The Government of Bali decided that culture tourism concepts were viewed as the ideology, spirit, guidelines, framework and solutions in developing tourism in Bali. These decisions were then legitimized in a form of provincial rules